Volatile organic compounds exposure associated with frailty in United States adults from NHANES 2011–2018 - Qu, Tian-Zhen; Zhang, Tian; Huang, Qing-Yun; Chen, Xing-Lan; Zhu, Ye (Frontiers in Public Health, 2025)
BackgroundWhether environmentally relevant exposure to volatile organic compounds (VOCs) contributes to frailty remains unknown. We examined urinary VOC metabolites (VOCms) and their mixtures in relation to frailty in a nationally representative U.S. cohort.MethodsWe analysed 2,715 adults (≥ 20 y) from NHANES 2011–2018 in a cross-sectional design. Frailty was defined with a 48-item index. Sixteen creatinine-adjusted VOCms were quantified. Single metabolites were evaluated with survey-weighted logistic regression. Two-directional weighted-quantile-sum regression (WQS), grouped Bayesian kernel machine regression (BKMR) and quantile g-computation (qgcomp) characterized mixture effects, and sex- and age-stratified subgroup analyses were performed. Mediation by γ-glutamyl-transferase (GGT), bilirubin, albumin, the Dietary Oxidant/Antioxidant Balance Score (OBS), and high-sensitivity C-reactive protein (hs-CRP) was assessed.ResultsFour metabolites—DHBMA, CEMA, HPMMA and MHBMA3—were each positively associated with frailty (adjusted OR per log₁₀-unit 1.67–2.59). The positive WQS index increased frailty odds by 25% (OR = 1.25, 95% CI 1.17–1.33), whereas the negative index lowered odds by 17% (OR = 0.83, 0.75–0.91). Only the positive index remained significant in men and in adults ≥ 65 y; MHBMA3 dominated male weights (18%), HPMMA female weights (16%). BKMR confirmed a monotonic dose–response for the positive group, whereas qgcomp detected no overall effect. Bilirubin and albumin jointly mediated 5–20% of the associations; GGT showed no significant mediation.ConclusionUrinary VOCm mixtures are linked to frailty at population exposure levels, with risk driven by four metabolites and most pronounced in men and older adults. Oxidative stress explains part—but not all—of the association, suggesting additional pathways. Reducing VOC exposure may help preserve physiological reserve; longitudinal studies are warranted to confirm causality.